2013
DOI: 10.12681/mms.383
|View full text |Cite
|
Sign up to set email alerts
|

Introduced marine species in Croatian waters (Eastern Adriatic Sea)

Abstract: The Croatian part of the Adriatic Sea covers more than 35% of the total Croatian territory, which means that monitoring changes in marine ecosystems and the conservation of biodiversity are of great importance. Following global changes, Croatia is experiencing increasing problems due to the introduction of new species that include aliens (due to aquaculture activities and shipping) and species from other Mediterranean subregions that are extending their geographic range. This work provides a checklist of intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…The Adriatic Sea counts more than 190 non-indigenous species [74]. In the Italian northern Adriatic 51 invasive species (39 of which in the Lagoon of Venice) have been recorded since 1945 [75], while 61 alien species (due to aquaculture activities and shipping) and 52 introduced (due to climate change) were recorded in Croatian waters [76]. Some invasive species, such as the green grape algae Caulerpa cylindracea and the red algae Womersleyella setacea, are known as habitat modifiers, reducing diversity and changing community structure in invaded areas compared to non-invaded sites [77].…”
Section: Benefitsmentioning
confidence: 99%
“…The Adriatic Sea counts more than 190 non-indigenous species [74]. In the Italian northern Adriatic 51 invasive species (39 of which in the Lagoon of Venice) have been recorded since 1945 [75], while 61 alien species (due to aquaculture activities and shipping) and 52 introduced (due to climate change) were recorded in Croatian waters [76]. Some invasive species, such as the green grape algae Caulerpa cylindracea and the red algae Womersleyella setacea, are known as habitat modifiers, reducing diversity and changing community structure in invaded areas compared to non-invaded sites [77].…”
Section: Benefitsmentioning
confidence: 99%
“…Successfully invading thermophilic species are expected to take advantage of increased average temperatures (Dulčić and Grbec, 2000; UNEP -MAP -RAC/SPA, 2008; Dulčić et al, 2010Dulčić et al, , 2011Brotz and Pauly, 2012;Zenetos et al, 2012;Pecarevič et al, 2013) but they also need to either find or make trophic niche space, such as by outcompeting native species (e.g., Pranovi et al, 2003). Meanwhile, some local native species might be negatively affected by higher temperatures, but may be able to exploit new trophic opportunities as a trade-off.…”
Section: Introductionmentioning
confidence: 99%
“…They are found around aquaculture areas and they can attach to the vessels. It is highly likely that human activities may induce their spread to nonnative ecosystems (Pecarevic et al, 2013). Therefore, it can be concluded that the transportation and spread of C. gigas to the Marmara Sea have probably occurred via vessels or water currents (Albayrak, 2011); the international maritime traffic being probably the main factor.…”
Section: Discussionmentioning
confidence: 99%